Evaluation of haemagglutination and haemagglutination inhibition tests with Indian isolates of bovine herpesvirus-1 - Pandey, A B; Mehrotra, M L; Negi, B S (The Indian Journal of Animal Sciences, 2012)
Indian isolates of bovine herpesvirusÂ·1 (BHV - 1) of respiratory and genital tract origin were evaluated for their haemagglutinating (HA) activity using C 57 BL mouse red blood cells. The antisera raised in rabbits against the isolates gave similar haemagglutination inhibition (HI) activity with either of these isolates. The HI and serum neutralization titres of the isolates were also comparable.